Quinapril treatment abolishes diabetes-associated atherosclerosis in RAGE/apolipoprotein E double knockout mice - Watson, Anna M. D.; Li, Jiaze; Samijono, Dian; Bierhaus, Angelika; Thomas, Merlin C.; Jandeleit-Dahm, Karin A. M.; Cooper, Mark E. (Atherosclerosis, 2014)
Objective/Rationale - Both the renin-angiotensin system (RAS) and the receptor for advanced glycation end products (RAGE) potentiate diabetes-associated atherosclerosis (DAA). We assessed the effectiveness of concomitant RAS and RAGE inhibition on DAA. - Methods - Diabetic (5 × 55 mg/kg streptozotocin daily) and non-diabetic male RAGE/apolipoprotein E double knockout (RAGE/apoE DKO) mice were treated with quinapril (30 mg/kg/day) for 20 weeks. At the end of the study aortic plaques were assessed. - Results - Diabetic RAGE/apoE DKO showed significantly less plaque area than diabetic apoE KO mice. Plaque deposition was almost abolished in quinapril treated diabetic RAGE/apoE DKOs, with significant attenuation of vascular collagen deposition, nitrotyrosine staining, and reduced macrophage infiltration. Expression of the advanced glycation end product receptor 3 (galectin 3) was also significantly reduced. - Conclusion - Concomitant inhibition of RAS and RAGE signalling almost completely inhibited the development of experimental DAA. A dual therapeutic approach may be a superior strategy for the treatment of diabetic macrovascular disease..
Gesehen am 27.08.2020